Investigation of the Effects of Unbalance and Bearing Wear on Shaft Vibration in a Natural Gas Turbine Plant - Nayeeif , Adil Abed; Al-Ameen, Ehsan S.; Jebur, Nazik Abdulwahid; Farhan Ogaili, Ahmed Ali; Hamdan , Zahra Khalid; Njim, Emad Kadum (Applied Science and Engineering Progress, 2025)
This work investigates the effect of imbalance and bearing wear on the vibration of rotating shafts at a southern Iraqi natural gas liquefaction plant. This experimental study examines the impact of wear on couplings and uneven weight on the vibration of a two-stage gas turbine’s shaft, taking measurements during operation. The experimental procedure involves the use of proximity probes and the ADRE-408 Bentley Nevada system to measure vibrations along the X and Y axes. The study focuses on a two-stage gas turbine supported by four journal bearings and analyses the effects of coupling imbalance and erosion. The results show that adding 10 g and 20 g weights at 0° and 30° anticlockwise considerably increases the vibration amplitude, from 22.46 µm at 113.75 Hz to 24.35 µm at 117.5 Hz. Replacing worn couplings and bearings led to system stabilisation, vibration reductions, and a shift in critical frequencies. The data confirm that mass loss and bearing wear greatly affect the dynamics of rotating machinery. These findings emphasise the importance of predictive maintenance and diagnostic monitoring to prevent mechanical failures and maintain system stability.